Enhancing English Proficiency Through the 'One Day in English' Program: A Case Study at SMAN 1 Sidrap - Sitti Aisa; Sam Hermansyah; Syeh Junaidi Usman; Citra Karisma; Kartini; Muhammad Anugrah Nasruddin (Universitas Muhammadiyah Enrekang, 2025)
English proficiency is a crucial skill in the era of globalization, yet high school students often face challenges in actively practicing the language. This study examines the implementation and effectiveness of the